2009
DOI: 10.1017/s0016756809006268
|View full text |Cite
|
Sign up to set email alerts
|

New carbon isotope stratigraphy of the Ediacaran–Cambrian boundary interval from SW China: implications for global correlation

Abstract: The Yangtze Platform preserves relatively thick carbonate successions and excellent fossil records across the Ediacaran–Cambrian boundary interval. The intensely studied Meishucun section in East Yunnan was one of the Global Stratotype Section candidates for the Precambrian–Cambrian boundary. However, depositional breaks were suspected in the section and the first appearance of small shelly fossils could not be verified. The Laolin section located in NE Yunnan is more continuous and shows great potential for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 42 publications
4
63
0
3
Order By: Relevance
“…Similar isotopic compositions of kerogen, carbonates and oil from Infracambrian-Cambrian strata are also reported in numerous areas including Oman, Pakistan, North West Indian, Morocco, Siberia and USA (Hoering, 1967;Welte et al, 1975;Tucker, 1986;Fowler and Douglas, 1987;Brasier et al, 1990;Summons and Powell, 1992;Peters et al, 1995;Bazhenova and Arefiev, 1998;Li et al, 2009a;Kaufman and Knoll, 1995;Walter et al, 2000). Summons and Powell (1992) suggested that during Cambrian, elevated atmospheric carbon dioxide levels resulted in higher fractionation during photosynthesis.…”
supporting
confidence: 53%
“…Similar isotopic compositions of kerogen, carbonates and oil from Infracambrian-Cambrian strata are also reported in numerous areas including Oman, Pakistan, North West Indian, Morocco, Siberia and USA (Hoering, 1967;Welte et al, 1975;Tucker, 1986;Fowler and Douglas, 1987;Brasier et al, 1990;Summons and Powell, 1992;Peters et al, 1995;Bazhenova and Arefiev, 1998;Li et al, 2009a;Kaufman and Knoll, 1995;Walter et al, 2000). Summons and Powell (1992) suggested that during Cambrian, elevated atmospheric carbon dioxide levels resulted in higher fractionation during photosynthesis.…”
supporting
confidence: 53%
“…The majority of bilaterian skeletal fossils of the Terreneuvian Series belong to these latter groups. Their first appearances occurred in beds younger than the Precambrian-Cambrian boundary and the carbon isotope negative anomaly associated with this boundary (Narbonne, Kaufman & Knoll, 1994;Brasier et al 1996;Kimura et al 1997;Li et al 2009), but not younger than those with Siberian δ 13 C feature Z and attributed to the upper Anabarites trisulcatus-lower Purella zones of the NemakitDaldynian Stage (Brasier, Khomentovsky & Corfield, 1993;Brasier, et al 1994a,b). These first appearances can be correlated with the Anabarites trisulcatusProtohertzina anabarica (SSF1) Assemblage Zone of the lower Meishucunian Stage of South China, where all of them except shells of molluscs occur in beds older than the tuffite with a combined depositional age of 535.2 ± 1.7 Ma (Zhu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They are correlated bio-and chemostratigraphically with the Nemakit-Daldynian Stage of Siberia (Qian et al 2002;Li et al 2007Li et al , 2009Li & Xiao, 2004;Steiner et al 2007) and comprise in ascending order the assemblage zones Anabarites trisulcatusProtohertzina anabarica (SSF1) of the lower Meishucunian Stage, Paragloborilus subglobosus-Purella squamulosa (SSF2) and Watsonella crosbyi (SSF3) of the middle Meishucunian Stage (Fig. 3).…”
Section: D South China India and Iranmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest records might be the work in Morocco [1], Siberia [2], and subsequently South China [3]. So far, data of the carbon chemostratigraphy have covered most of the continents [2,[4][5][6][7][8][9][10][11][12][13]. Most of the results are regional, the sampled sections or drilling cores are always limited to parts of the Cambrian System, so carbon isotope data in the Cambrian are inevitably scattered.…”
mentioning
confidence: 99%